Custos indiretos na construção civil: contribuição aos processos de orçamentação e controle de custos em empreendimentos residenciais verticais - Azevedo, Odélia Geiza Nobre (2006)
Intense and constant technological and economic changes brought by the globalization ask for the companies to be more and more competitive, working for an increasing performance of its production and sells. As a consequence, costs reduction is fundamentally important. In this context, there are also civil construction companies, that are responsible for a significant parcel of the Brazilian economy, specially the one related to the housing that has not only direct repercussion in the economic development, but also in the social one. Facing the difficulties in the identification and allocation of the indirect costs and what they represent to the amount cost of a product, the main purpose of this research is to show how the analysis of the indirect costs composition can refine home building budget and cost control. It is an empirical research with explorer and qualitative characteristics, and it was developed using the case study strategy. Thus, it had been chosen concluded home buildings, from distinct companies, in which its indirect costs were identified, in order to begin the analysis of incurred indirect costs in comparison to the estimated ones. It had been proceeded a bibliographical revision regarding the subject, and documents and archives were collected, in addition, there had been interviewed the production director, engineer of planning and accountant from the companies of the study, besides comments, that had evidenced adversities and suggestions to the budget and indirect costs control, and which elements from that cost could be reduced. The results also showed that with a critical budget of the indirect cost it is possible to analyze and control the costs, as well as planning the home building cash flow, in order to have a good management of costs and efficient decisions.